2018
DOI: 10.1186/s13006-018-0153-1
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding knowledge and attitudes of health professional students: a systematic review

Abstract: BackgroundBreastfeeding support from health professionals can be effective in influencing a mother’s decision to initiate and maintain breastfeeding. However, health professionals, including nursing students, do not always receive adequate breastfeeding education during their foundational education programme to effectively help mothers. In this paper, we report on a systematic review of the literature that aimed to describe nursing and other health professional students’ knowledge and attitudes towards breastf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
1
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 34 publications
8
60
1
15
Order By: Relevance
“…Although students felt prepared to identify benefits of breastfeeding, their confidence to perform breastfeeding skills was low.. This is concordant with a systematic review of healthcare students demonstrating insufficient breastfeeding knowledge regarding assessment and management of breastfeeding-related issues [25]. A study in the USA found 100% nursing students were able to identify breastmilk as the optimum feeding choice, however 65% were unable to identify cracked nipples as a potential indication poor latching, with 62% believing cracked nipples are managed by expressing milk and refraining from breastfeeding for 24 h [26].…”
Section: Discussionsupporting
confidence: 71%
“…Although students felt prepared to identify benefits of breastfeeding, their confidence to perform breastfeeding skills was low.. This is concordant with a systematic review of healthcare students demonstrating insufficient breastfeeding knowledge regarding assessment and management of breastfeeding-related issues [25]. A study in the USA found 100% nursing students were able to identify breastmilk as the optimum feeding choice, however 65% were unable to identify cracked nipples as a potential indication poor latching, with 62% believing cracked nipples are managed by expressing milk and refraining from breastfeeding for 24 h [26].…”
Section: Discussionsupporting
confidence: 71%
“…The current systematic review was reported using the Preferred Reporting Items for Systematic Reviews and meta-analysis (PRISMA) [23]. We searched published literature using the PubMed, Web of Science, Google Scholar, Embase, Science direct, and Cochrane library databases.…”
Section: Searching Strategiesmentioning
confidence: 99%
“…However, health professionals, do not always receive adequate breastfeeding education during their foundational education programme to effectively help mothers. Studies done on the knowledge, attitude and practice of medical and nursing students from different parts of the world showed that a lot more need to be done in educating and building the capacity of health professionals [26][27][28][29][30]. The knowledge of the students was mostly average and they were low for those in preclinical school.…”
Section: Introductionmentioning
confidence: 99%